2023
DOI: 10.1177/21582440221148379
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, Interpersonal Communication Competence, and Media and Technology Usage as Predictors of Loneliness Among University Students

Abstract: Loneliness is a common concern among university students, as these individuals experience many of the risk factors associated with loneliness. This experience of loneliness tends to lead to numerous consequences such as negative self-evaluations, anxiety, and depression, which in turn lead to impaired concentration and a decline in academic motivation and performance. The overarching aims of this study were to identify the predictor variable(s) or combination of predictor variables, namely self-esteem, interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 89 publications
(175 reference statements)
0
0
0
Order By: Relevance
“…Many studies have defined loneliness, with a standard definition explaining it as a subjective psychological state in which a person feels lonely when social relationships are less desirable [3]; this suggests that loneliness occurs when there is a discrepancy between people's social relationships and the relationships they psychologically desire [7]. Therefore, loneliness is also considered a unique state in which a person who feels lonely, even amid a crowd, feels subjectively isolated and that existing social relationships do not meet his or her needs [9].…”
Section: Lonelinessmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have defined loneliness, with a standard definition explaining it as a subjective psychological state in which a person feels lonely when social relationships are less desirable [3]; this suggests that loneliness occurs when there is a discrepancy between people's social relationships and the relationships they psychologically desire [7]. Therefore, loneliness is also considered a unique state in which a person who feels lonely, even amid a crowd, feels subjectively isolated and that existing social relationships do not meet his or her needs [9].…”
Section: Lonelinessmentioning
confidence: 99%
“…Time spent on social media may act as a moderator of the age-loneliness relationship. Few studies have included children because of the restrictions on their access to social media [3]. Previous research has not shown a correlation between the usage of social media by youngsters and feelings of loneliness or isolation.…”
Section: Impact Of Age and Gender Of Social Media Use On Feelings Of ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interpersonal communication skills apply to any condition [2]. A person with less interpersonal communication competence often exhibits lower self-esteem [3,4]. According to Wang et al [5], interpersonal communication can increase social support while creating social harmony.…”
Section: Introductionmentioning
confidence: 99%